Digital Business Transformation before Disruption - จอนจวบทรง, ลั่นทม; ธรรมบุญวริศ, ณธภร (Business Administration and Management Journal Review, 2019)
Digital business is focused on operating business processes on digital systems or platforms. It comprises a few physical resources but it is focused on creativity to produce products or services which matches to customers’ demand. Furthermore, the digital business model have emerged and become the focal points of certain businesses. Thus, digital businesses could disrupt traditional businesses. The digital businesses have to focus on rapid emerging with agile business analysis and business planning.